Tracking the Course of Fibrodysplasia Ossificans Progressiva in a Patient with the Classic ACVR1 Mutation - Mohamed Mostafa Kotb; Usama Farghaly Omar; Bishoy Raafat Zaky; Arun-Kumar Kaliya-Perumal (BioMedicine, 2026)
Fibrodysplasia Ossificans Progressiva (FOP) is an extremely rare and debilitating genetic disease affecting approximately 1 in 2 million people. It is caused by a heterozygous gain-of-function mutation in the gene encoding activin A receptor type I (ACVR1), leading to dysregulated bone morphogenetic protein (BMP) signaling. Clinically, the disease features progressive heterotopic ossification, with bone forming in sites of soft tissue inflammation. We report a 7-year-old boy with two isolated ectopic bone masses in the paraspinal muscles of the neck and lumbar spine, resulting in pain and restricted spinal mobility. Genetic analysis revealed the classic c.617G>A mutation in the gene encoding ACVR1, causing an R206H substitution within the intracellular glycine-serine (GS) domain, thereby confirming the diagnosis of FOP. The inflammatory flare was managed with nonsteroidal anti-inflammatory drugs, and the patient continues to undergo regular clinical monitoring for new lesions. Palovarotene, a retinoic acid receptor-γ (RARγ) agonist, has demonstrated a 54% reduction in the annualized volume of heterotopic ossification in Phase III trials; however, access remains limited to certain regions and was unavailable to this patient; thus, his condition was managed conservatively. This case highlights the importance of early recognition and molecular confirmation of FOP to guide management. Symptomatic treatment and vigilant monitoring remain essential, although emerging pharmacological therapies offer promise. Broader access to these therapies may improve outcomes and ensure that patients worldwide receive effective treatment for this rare condition.